The 2015 Student Mobilizations in South Africa. Contesting Post-Apartheid Higher Education - Cini, Lorenzo (PARTECIPAZIONE E CONFLITTO, 2019)
In October 2015, a student protest at the University of the Witwatersrand (WITS), a historically white university (HWU), arising in opposition to the decision taken by the University Council to increase tuition fees, spurred a massive wave of mobilizations across the country. The protests drew national and international media attention to what became the #FeesMustFall movement, named after the most popular twitter hashtag adopted by the protesters. Why did a local mobilization at WITS in 2015 trigger a national wave of student protests? After ten days of protests, the South African President intervened directly to calm down the situation by announcing a 0% increase in tuition fees for 2016. To all appearances, ten days of protests allowed South African students to win their battle over the hike in tuition fees. How and why did they obtain this concession? To answer the questions above, I have combined various qualitative methods of analysis. I carried out several in-depth interviews with relevant actors involved in the issue; I analysed movement documents elaborated by the students in the year of the protest (2015) as well as the main policy documents on higher education in post-apartheid South Africa (1994-2016) released by the government.